2021
DOI: 10.1016/j.ijpsycho.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Resting state heart rate variability and false memories

Abstract: Recent studies have shown higher resting-state vagally-mediated heart rate variability (vmHRV) to be related to greater memory retrieval. Research has not yet linked resting vmHRV with memory encoding and retrieval, as both are thought to play an important role in correctly distinguishing between true and false memories. The current study investigated this possible link in n = 71 undergraduate students. VmHRV was assessed during a 5minute resting baseline period. Participants then completed the Deese-Roediger-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
1
8
1
Order By: Relevance
“…This suggests that neurophysiological stimulation and not any placebo effect triggered cognitive enhancement. This idea is in line with previous findings that demonstrated a link between vagally mediated HRV and selective attention ( Giuliano et al, 2018 ) as well as with the discrimination performance of false from true memories ( Feeling et al, 2021 ). A change of response strategy that may change the interpretation of these results seems unlikely as speed and accuracy with respect to go-/no-go responses during the Sustained Attention to Response Task did not change from pre- to post-test in either group.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that neurophysiological stimulation and not any placebo effect triggered cognitive enhancement. This idea is in line with previous findings that demonstrated a link between vagally mediated HRV and selective attention ( Giuliano et al, 2018 ) as well as with the discrimination performance of false from true memories ( Feeling et al, 2021 ). A change of response strategy that may change the interpretation of these results seems unlikely as speed and accuracy with respect to go-/no-go responses during the Sustained Attention to Response Task did not change from pre- to post-test in either group.…”
Section: Discussionsupporting
confidence: 92%
“…Studies examining the impact of HRV during wakefulness on episodic LTM also show mixed results. One study demonstrated that people with poor vagal autonomic functioning (low resting HRV) show greater false memory errors ( 102 ). In addition, cardiac vagal tone has been shown to positively correlate with better memory for emotionally charged stimuli ( 103 , 104 ), albeit no relation with memory for neutral stimuli.…”
Section: Cns and Ans Contributions To Long-term Memorymentioning
confidence: 99%
“…Moreover, RMSSD was not linked to cognitive control over long-term memory. Contrary to this work, previous studies assessing cognitive control over long-term memory (Feeling et al, 2021;Gillie et al, 2014Gillie et al, , 2015Magnon et al, 2022) did not consider repeated measures over the same experimental session. An exploratory analysis (Data S8-SR3) revealed that the psychophysiological relationship changed over repeated measures due to baseline changes in cardiac control (i.e., mean heart rate and RMSSD).…”
Section: Vmhrv Does Not Correlate To Cognitive Control Over Long-term...mentioning
confidence: 73%
“…Consequently, based on theoretical and structural ties, cardiac vagal control indexed by vmHRV should be associated with cognitive control over memory. One study recently demonstrated such a link between resting-state vmHRV with the production of false memories using the DRM task (Feeling et al, 2021). However, like in most HRV studies, the correlation between cognitive functioning and vmHRV was established for physiological measures recorded only at resting-state.…”
Section: Introduction 1| Autonomic and Cognitive Controlmentioning
confidence: 99%